High tibial osteotomy in cartilage repair - Awang, Mohd Shukrimi; Manivannan, Sureshbabu; Lee, Joel; Hui, James H.P. (Sprnger Link, 2014)
Deformity of the knee associated with osteoarthrosis (OA) is a common presenting complaint to the orthopedic surgeon. In a normal knee, approximately 60 % of the weight-bearing forces are transmitted through the medial compartment and 40 % through the lateral compartment. The varus knee with unicompartmental OA of the medial compartment has an altered limb alignment and subsequently more load is distributed to the affected compartment. Despite the expanding indications for knee arthroplasty, it is advantageous to delay arthroplasty given the higher wear rate and likelihood of future complex revisions if the primary surgery is performed in patients at a young age [1]. Proximal tibial osteotomy, a joint-preserving procedure, has been reported as a viable surgical option for younger patients with isolated medial compartment arthritis. The aim of the surgery is to shift the weight-bearing axis away from the diseased area, as this relieves the pain and suppresses the disease progression. It has been reported that young active patients with isolated medial compartment disease and varus knee alignment have the highest likelihood of a good outcome with an osteotomy [2, 3]. This can delay, or potentially avoid, the need for a total knee arthroplasty.